On-Campus Field Experiences Help Students to Learn and Enjoy Water Science During the COVID-19 Pandemic - Saup, C.; Lamantia, K.; Chen, Z.; Bell, B.; Schulze, J.; Alsdorf, D.; Sawyer, A.H. (Frontiers in Environmental Science, 2022)
Online modes of teaching and learning have gained increased attention following the COVID-19 pandemic, resulting in education delivery trends likely to continue for the foreseeable future. It is therefore critical to understand the implications for student learning outcomes and their interest in or affinity towards the subject, particularly in water science classes, where educators have traditionally employed hands-on outdoor activities that are difficult to replicate online. In this study, we share our experiences adapting a field-based laboratory activity on groundwater to accommodate more than 700 students in our largest-enrollment general education course during the pandemic. As part of our adaptation strategy, we offered two versions of the same exercise, one in-person at the Mirror Lake Water Science Learning Laboratory, located on Ohio State University’s main campus, and one online. We used laboratory grades and a survey to assess differences in student learning and affinity outcomes for in-person and online exercises. Students who completed the in-person exercise earned better scores than their online peers. For example, in Fall 2021, the median lab score for the in-person group was 97.8%, compared to 91.7% for the online group. The in-person group also reported a significant (p < 0.05) increase in how much they enjoyed learning about water, while online students reported a significant decrease. Online students also reported a significant decrease in how likely they would be to take another class in water or earth sciences. It is unclear whether the in-person exercise had better learning and affinity outcomes because of the hands-on, outdoor qualities of the lab or because the format allowed greater interaction among peers and teaching instructors (TAs). To mitigate disparities in student learning outcomes between the online and in-person course delivery, instructors will implement future changes to the online version of the lab to enhance interactions among students and TAs.